Evaluation and Repair Case Study for Existing Structural Systems - Chandra, Shreya (Journal of Progress in Civil Engineering, 2025)
Civil Engineering Industry is one of the oldest industries which provide a basic infrastructure which give an essential framework to all the people. Structures can be any sort it tends to be Historical, Heritage Structure, Residential building, Commercial building or an Industrial building. Each structure has its own service life, and inside this service life, it should stand solidly on its position. A collapsed mechanism has increased and today’s Structures are getting collapsed before their service life. Therefore, it is advisable to monitor it periodically by taking a professional opinion. Structural Audit is a preliminary technical survey of a building to assess its general health as a civil engineering structure. It is normally started as the initial step for repair. The construction material mainly reinforced concrete is being used extensively for various types of construction projects. The structures become older, we find in them certain degradation or deterioration with resultant distress manifested in the form of cracking, spalling, dampness, corrosion etc. In the present time, there is the presence of defects in building as a result of low-quality control during the construction, lack of maintenance and an unfavorable change in the weather condition. It is essential to mai0ntain quality in terms of material quality, mixture with their desire specification, workmanship etc. The main purpose of repair and rehabilitation is the investigation of the present structures and suitable solution for the building defects, distresses and damages. In this project, some Non-destructive test and chemical tests will be done to check the quality and strength parameter of the present structure.